2005
DOI: 10.1099/mic.0.27715-0
|View full text |Cite
|
Sign up to set email alerts
|

Identity and effects of quorum-sensing inhibitors produced by Penicillium species

Abstract: Quorum sensing (QS) communication systems are thought to afford bacteria with a mechanism to strategically cause disease. One example is Pseudomonas aeruginosa, which infects immunocompromised individuals such as cystic fibrosis patients. The authors have previously documented that blockage of the QS systems not only attenuates Ps. aeruginosa but also renders biofilms highly susceptible to treatment with conventional antibiotics. Filamentous fungi produce a battery of secondary metabolites, some of which are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
289
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 418 publications
(298 citation statements)
references
References 56 publications
5
289
0
4
Order By: Relevance
“…It is likely that compound 5 (emodin) penetrated into the biofilm and interfered with bacterial intercellular communications, by which the QS system of P. aeruginosa was disturbed and repressed. Moreover, previous studies have found that QS-deficient P. aeruginosa has reduced tolerance to such antimicrobial compounds as tobramycin and H 2 O 2 (Bjarnsholt et al, 2005;Rasmussen et al, 2005b). In addition, the results also showed that compound 5 can inhibit formation of S. maltophilia biofilm (Fig.…”
Section: Discussionsupporting
confidence: 61%
“…It is likely that compound 5 (emodin) penetrated into the biofilm and interfered with bacterial intercellular communications, by which the QS system of P. aeruginosa was disturbed and repressed. Moreover, previous studies have found that QS-deficient P. aeruginosa has reduced tolerance to such antimicrobial compounds as tobramycin and H 2 O 2 (Bjarnsholt et al, 2005;Rasmussen et al, 2005b). In addition, the results also showed that compound 5 can inhibit formation of S. maltophilia biofilm (Fig.…”
Section: Discussionsupporting
confidence: 61%
“…QSI compounds, on the other hand, block or destroy the LuxR homologue proteins, resulting in a lowered overall concentration; hence the genes that require higher concentrations are the ones that are more readily inhibited. The QS-controlled genes PA2591, PA2163 and PA2570 (pa1L) identified by Rasmussen et al (2005b) support this. DNA array analysis of wild-type P. aeruginosa treated with different QSIs revealed that none of the compounds affected expression of PA2591, whereas PA2163 was downregulated by two inhibitors, 4-NPO and PA.…”
Section: Global Analysis Of Qsi Effectsmentioning
confidence: 54%
“…They utilize the V. fischeri LuxR or P. aeruginosa LasR and RhlR proteins as targets, whose activities can be assessed upon regulation of toxic gene products (phospholipase A or levansucrase) or reporter gene products (␤-galactosidase or green fluorescent protein). A clear demonstration of this system can be found in studies that tested 100 extracts from 50 species of Penicillium, finding that one-third of species produce QSI compounds, including penicillic acid and patulin (232). Staphylococcal AIP reporters that make use of genetic reporters, such as ␤-galactosidase fused to central virulence genes of the agr QS system, have also been developed, which have allowed, for example, the identification of trihydroxy methyl xanthones from fungal sources as inhibitors of AIP signaling (233).…”
Section: Natural-product Qs Inhibitorsmentioning
confidence: 99%
“…As such, QSI may render cells more susceptible to a variety of antimicrobial compounds. Two studies have recently assessed this possibility using QSI compounds found from natural sources together with tobramycin, a drug reported to inhibit biofilm development of P. aeruginosa QS mu-tants (232,250). In P. aeruginosa foreign-body infection models in mice, it was demonstrated that combinatorial treatments of tobramycin with either the furanone C-30, ajoene (from garlic), or horseradish extracts (with the major QSI component being iberin) all exhibited synergistic inhibitory activities toward viable bacterial cell counts when treatments were provided soon after implantation.…”
Section: Antibiotics As Qs Inhibitorsmentioning
confidence: 99%